Anthelmintic Effects of Alkylated Diamines and Amino Alcohols against Schistosoma mansoni. (19th August 2013) - Fernandes, Fábio de Souza; Rezende Júnior, Celso O.; Fernandes, Tayrine Silva; da Silveira, Lígia Souza; Rezende, Carlos A. M.; De Almeida, Mauro V.; de Paula, Renato G.; Rodrigues, Vanderlei; Da Silva Filho, Ademar A.; Couri, Mara R. C.
Abstract : Polyamines are substances involved in many aspects of cell growth, division, and differentiation. Because of the metabolic differences between host cells and parasite cells, polyamine metabolism has been considered as a potential target for the chemotherapy of parasitic diseases. The aim of this work was to evaluate the schistosomicidal activity of different N -alkylated diamines (3a –3h ), amino alcohols (4a –4d ), and glycosylated amino alcohols (10a –10d ). Compounds were prepared by synthetic methods and submitted to in vitro evaluation against adult worms of Schistosoma mansoni . At 100 μ M, 3b, 3e, and 3h as well as 4a, 4b, 4d, 10a, 10b, and 10d resulted in 100% mortality of adult schistosomes. Compound 3d (12.5 to 100 μ M) caused the death of 100% of both male and female adult schistosomes, while 3f (12.5 to 100 μ M) resulted in 100% mortality of only male adult worms, whereas no mortality in female worms was observed. Compounds 3d and 3f were also able to reduce viability and decrease production of developed eggs in comparison with the negative control group. Diamines 3d and 3f may represent useful lead compounds for further optimization in order to develop new schistosomicidal agents.